A model for cathodic blister growth in coating degradation using mesomechanics approach. Issue 5 (23rd November 2015) - Nazir, M. H.; Khan, Z. A.; Saeed, A; Stokes, K.
Abstract : The paper presents a novel theoretical model of blistering initiation and propagation especially useful for coating life assessment. The focus is on initially circular blisters. A two‐part theoretical analysis of blistering is conducted using mesomechanics approach coupling diffusion concepts with fracture mechanics concepts. The diffusion concept is used to treat the corrosive species transport, eventually causing corrosion and blistering, while the fracture mechanics concept is used to treat the blister growth as circular crack propagation. Effects of thickness ratio and modulus ratio on blistering propagation are discussed. A simple criterion is identified which excludes the possibility of widespread blister propagation. Furthermore, a comparative study with the existing blistering models is carried out. Experiments are reported for blistering using a model coating‐substrate system, chosen to allow visualisation of interface and to permit coupled (diffusion and residual) stresses in the coating over a full range of interest. The predicted limits from theoretical model are expected to be useful for the manufacturers in the design and deposition of coatings.